Pricing in a two-echelon supply chain with different market powers: Game theory approaches - Afshin Esmaeilzadeh; Ata Allah Taleizadeh (Journal of Industrial Engineering International, 2016)
In this research, the optimal pricing decisions for two complementary products in a two-echelon supply chain under two scenarios are studied. The proposed supply chain in each echelon includes one retailer and two manufacturers and the same complementary products are produced. In the first scenario, we assume the unit manufacturing costs of the complementary products in each echelon are the same, while in the second one the different unit manufacturing costs are supposed and lead to demand leakage from the echelon with the higher unit manufacturing cost to the echelon with the lower unit manufacturing cost. Moreover, under the second scenario, the products with lower price are replaced with the higher price products. The purpose of this study is to analyze the effects of different market powers between the manufacturers and the retailer and the demand leakage on the optimal wholesale and retail prices and also on the profit of the chain. The relationships between the manufacturers and the retailer are modeled by the MS-Stackelberg and MSBertrand game-theoretic approach where the manufacturers are leaders and the retailers are followers.
Keywords: 650; Pricing; Complementary products; Market power; MS-Stackelberg game; MS-Bertrand game